Boy Troubles? Male Literacy Depictions in Children's Choices Picture Books. (31st January 2017) - Gritter, Kristine; Van Duinen, Deborah Vriend; Montgomery, Kimberly; Blowers, Devony; Bishop, Dan
Abstract: This article is a critical content analysis of Children's Choice award‐winning picture books from 2000 to 2014. The "critical" part of the analysis consists of selecting archetypes for males presented in these texts based on applying feminist poststructuralist literacy theory that situates literacy and language at the center of gender identity manifestation. In this analysis, the dominant archetypes for male characters tended to be Wildman, Friend, and Creator. In many books, male protagonists used literacy to maintain or develop a positive identity throughout the plot of the book, as reading, writing, and symbolic communication increased choices for male characters and offered insight through language, often inspiring change. Our findings suggest that deficit views of young males' literacy practices still appear in award‐winning picture books but are becoming more complex and positive. This matters because picture books reveal values of literacy as characters read or write or engage in symbolic communication.